DEVELOPING STUDENTS' INTERCULTURAL COMMUNICATIVE COMPETENCE IN FOREIGN LANGUAGE CLASSROOM - Oksana Bahlai; Nataliya Machynska; Yuliia Matviiv-Lozynska; Olha Senkovych; Mariia Voloshyn (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
Current social and economic changes have significantly influenced the tourism industry worldwide turning it into a diversified sphere of activity aimed at servicing tourists and meeting their needs. As tourist travels continue to grow throughout the world, they cause extensive cross-cultural contacts between different language and cultural groups. Thus, higher educational establishments of tourism profile have an important task to train competent specialists able to interact effectively at the intercultural level. In our article, based on the experience of teaching master's degree students majoring in international tourism at Lviv Polytechnic National University, we analysed possibilities of ICC development in ESP classes by means of flipped classroom method, role plays, discussions and a special course "Cross-cultural communication in religious tourism" designed by the authors. As shown by the results of our study, the methods and resources used in our ESP classes may be particularly appropriate for the development of students' ICC because they provide the basis for intercultural communication, ensure the link between the learning and real life and thus make the development of ICC more meaningful to learners.